2022
DOI: 10.1109/access.2022.3144681
|View full text |Cite
|
Sign up to set email alerts
|

CES Blocks—A Novel Chaotic Encryption Schemes-Based Blockchain System for an IoT Environment

Abstract: With the advent of the Internet of Things (IoT), smart devices have now changed their dimensions to provide applications in different domains such as medical, agriculture, and Industry 4.0. Although IoT provides more diversified applications, enhancing the security in IoT remains on the darker side of the research. Traditional IoT systems involve a third party to secure sensitive data during transmission in an IoT environment which can lead to complex and serious problems. To overcome security issues and eradi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…Vangala et al designed a new authenticated key agreement mechanism envisioned in smart contract-based blockchains in the context of smart agriculture to enhance the persistence and auditability of data stored in blocks [ 45 ]. Durga et al proposed a novel chaotic encryption-based blockchain IoT architecture to ensure data security and privacy in fields such as agriculture [ 46 ]. In the practical application of blockchain, the secure interaction of data is conducive to building trust among blockchain users, and the promotion and use of blockchain in the field of agricultural products and food.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Vangala et al designed a new authenticated key agreement mechanism envisioned in smart contract-based blockchains in the context of smart agriculture to enhance the persistence and auditability of data stored in blocks [ 45 ]. Durga et al proposed a novel chaotic encryption-based blockchain IoT architecture to ensure data security and privacy in fields such as agriculture [ 46 ]. In the practical application of blockchain, the secure interaction of data is conducive to building trust among blockchain users, and the promotion and use of blockchain in the field of agricultural products and food.…”
Section: Literature Reviewmentioning
confidence: 99%
“…References [ 40 , 41 , 42 , 43 ] innovated and improved the blockchain architecture, but lacked details regarding the application, such as security, consensus efficiency, etc. References [ 44 , 45 , 46 , 47 , 48 , 49 ] improve the secure interaction of data and the efficiency of consensus, but the blockchain architecture they adopt renders it difficult to carry the complex data characteristics of agricultural and food supply chains. However, the increasingly frequent and diverse data requests and operations in the rice supply chain urgently need to improve the application of blockchain, mainly in the following aspects.…”
Section: Introductionmentioning
confidence: 99%
“…The providers' and requesters' data stored in the blockchain nodes (60). To maintain data privacy, only learning models are shared instead of original data information (61). In the first phase, each hospital uploads the image datasets for collaboratively learning.…”
Section: Blockchain-based Data Sharing Processmentioning
confidence: 99%
“…Xu et al think that for the legal digital currency of "domestic type", we should first define the legal attribute of digital currency in China, divide it into payment token and stable token, and adopt different ways to improve these two tokens [21]. Durga et al suggested that a risk compensation mechanism should be established to make users aware of the defects of blockchain technology, and then implement supervision in a controllable scenario [22]. Khan et al believe that the healthy development of digital currency needs to speed up the expansion of digital currency's application scope and improve the financial supervision system on the premise of keeping pace with the development of digital technologies such as blockchain, so as to keep the forward-looking technology such as blockchain [23].…”
Section: Related Workmentioning
confidence: 99%